Chapter Nature-Inspired Nanotechnology and Smart Magnetic Activation: Two Groundbreaking Approaches Toward a New Generation of Biomaterials for Hard Tissue Regeneration - Sprio, Simone (InTechOpen, 2016)
Diatomite is a natural porous silica material of sedimentary origin, formed by remains of diatom skeletons called "frustules." The abundance in many areas of the world and the peculiar physico-chemical properties made diatomite an intriguing material for several applications ranging from food production to pharmaceutics. However, diatomite is a material still rarely used in biomedical applications. In this chapter, the properties of diatom frustules reduced to nanoparticles, with an average diameter less than 350 nm, as potential drug vectors are described. Their biocompatibility, cellular uptake, and capability to transport molecules inside cancer cells are discussed. Preliminary studies of in vivo toxicity are also presented.